Pengembangan Ekonomi Kreatif Desa (Studi Atas Pengembangan Ekowisata Cengklik, Blora) - Muhammad Mustaqim (Jurnal Perspektif)
The creative economy is a new feature of the information technology era. Ecotourism is one of the developments of the tourism sector that emphasizes conservation and the environment. “Cengklik” Mountain Ecotourism, in this case, is an effort to develop the village’s creative economy, which is driven by millennial generation youth. With a descriptive qualitative approach, several strategies for the development of “Cengklik” Mountain ecotourism were obtained, namely by innovating and developing creativity that was able to attract visitors, make massive promotions, add attractive spots, socialization and development, reforestation, cooperation with other parties, and procurement of sanitation facilities and pointing maps.